Is sport good for older adults? A systematic review of psychosocial outcomes of older adults' sport participation. Issue 1 (1st January 2017) - Gayman, Amy M.; Fraser-Thomas, Jessica; Dionigi, Rylee A.; Horton, Sean; Baker, Joseph
ABSTRACT: Although sport is promoted as a vehicle to enhance health and well-being throughout the life course, little is known about the psychosocial benefits and costs associated with sport participation in older adulthood. A mixed studies systematic review of English-language, peer-reviewed, original research articles (from the earliest record until March 2015) was undertaken to identify psychosocial outcomes of sport for adults over age 65 and to determine whether sport provides psychosocial outcomes that are distinct from other forms of physical activity. Results suggest sport involvement later in life was related to ageing, cognitive/perceptual, emotional, social, and motivational outcomes but it remains unclear whether these effects were solely related to participation in sport. Additional work with increased attention to methodological design and participant recruitment is needed to better understand psychosocial outcomes of older adults' sport participation and to inform potential interventions. Recommendations to enhance the quality of future studies in the area are discussed.